2020
DOI: 10.1002/dys.1669
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of systematized phonics on reading proficiency in Swedish second grade poor readers: Effects on pseudoword and sight word reading skills

Abstract: The aim of the present study was to evaluate the effect of systematized phonics on word reading in Swedish second grade poor readers. Forty-nine children who performed at or below the 25th percentile on pseudoword reading and/or sight word reading at the beginning of second grade participated in the study. The study had a cross-over design exploring within-and between-group effects of two different conditions: systematized phonics and classroom instruction. Overall, systematized phonics proved more effective t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The outcomes from reading study underscore that phonics is an effective method of reading instruction in the Swedish orthography, as indicated from previous research (Levlin & Nakeva von Mentzer, 2020;Wolff, 2011). Intense word reading practice based on explicitly training PA accompanied with letters, analyzing and segmenting sounds had a substantial effect on reading comprehension in this intervention.…”
Section: Theoretical Implicationssupporting
confidence: 65%
See 1 more Smart Citation
“…The outcomes from reading study underscore that phonics is an effective method of reading instruction in the Swedish orthography, as indicated from previous research (Levlin & Nakeva von Mentzer, 2020;Wolff, 2011). Intense word reading practice based on explicitly training PA accompanied with letters, analyzing and segmenting sounds had a substantial effect on reading comprehension in this intervention.…”
Section: Theoretical Implicationssupporting
confidence: 65%
“…In Sweden, a few quasi-randomized and randomized controlled studies conducted in schools were built on explicitly teaching phonics to students with reading difficulties. In a second grade, one-on-one intervention (Levlin & Nakeva von Mentzer, 2020) and in a third grade program (Wolff, 2011), the interventions yielded strong to small effects favoring the intervention groups compared to controls. The Levlin and Nakeva von Meltzer study showed, compared to Wolff, strong effects on decoding, which they attributed to the focused intervention on decoding skills.…”
Section: Phonicsmentioning
confidence: 96%
“…Such information could be informative considering the intervention group's substantial improvement in word recognition, since it reflects the quality of and access to orthographic representations of lexically stored words (Cunningham et al, 2001). Recently, in a Swedish quasi‐experimental second‐grade study Levlin and Nakeva von Mentzer (2020) suggested systematic phonics should be made a mandatory practice in early elementary school. We consider it well justified to recommend explicit phonics as a supplemental special education intervention to accelerate word decoding and word recognition in young Swedish students.…”
Section: Discussionmentioning
confidence: 99%
“…Code-based instruction has traditionally been taught in Scandinavian/Nordic elementary classrooms, but teaching phonics has rarely been evaluated for effectiveness in Swedish educational research (Levlin & Nakeva von Mentzer, 2020;Pontoppidan et al, 2018;Taube et al, 2015). To date, only three RCTs of reading interventions representing semi-transparent Swedish, Norwegian, and transparent Finnish orthography have been reported (Saine et al, 2011;Solheim et al, 2018;Wolff, 2011Wolff, , 2016.…”
Section: Phonics In Semi-transparent Orthographiesmentioning
confidence: 99%
See 1 more Smart Citation